Highly efficient one-pot assembly of peptides by double chemoselective coupling. Issue 36 (22nd August 2017) - Sampaio-Dias, Ivo E.; Sousa, Carlos A. D.; Silva-Reis, Sara C.; Ribeiro, Sara; García-Mera, Xerardo; Rodríguez-Borges, José E.
Abstract : An efficient and faster methodology for the assembly of oligopeptides by a three-step one-pot protocol with high yields and virtually no epimerization. Abstract : This study describes a methodological advancement in solution-phase peptide synthesis via the development of a convenient and operational protocol to synthesize oligopeptides in a one-pot three-step cascade method, in which two peptide bonds are introduced chemoselectively. Tri- to hexapeptides were obtained in high global yields (80–95%) with virtually no epimerization as determined via HPLC. The methodology described herein represents a faster, easier and milder approach to the synthesis of peptides, and it operates at equimolar amounts. This protocol comprises the formation of secondary and tertiary amides and is compatible with Z, Boc and Fmoc N -protecting groups as well as the use ofd /l and non-proteinogenic amino acids.